Adverse events of targeted therapies approved for women's cancers - Mathilde Saint-Ghislain, MD; Chloé Levenbruck, PhD; Audrey Bellesoeur, MD (Wolters Kluwer, 2021)
Breast cancer and gynecologic cancers affect >3 million women worldwide each year. With advances in precision medicine, a growing number of targeted therapies have been approved recently, and new therapeutic classes have emerged, including cell cycle inhibitors for hormone receptor positive breast cancer, antibody drug conjugate for human epidermal growth factor receptor 2 positive and triple negative breast cancer, and poly-ADP-ribose polymerase inhibitors for ovarian cancer. This article focuses first on the challenges for health care systems to address the specificities of each emerging targeted therapy and new issues raised by oral antitumor treatments, including individualization of prescriptions, drug-drug interaction assessment, pharmaceutical counseling, patient education, and outpatient management. Then, we provide an overview of the main adverse effects of targeted therapies approved for breast and gynecologic cancers, such as hematologic toxicity of cyclin-dependent kinase 4/6 inhibitors and poly-ADP-ribose polymerase inhibitors, metabolic disorders of phosphatidylinositol-3-kinase/Akt/mammalian target of rapamycin inhibitors, and cardiovascular toxicity of agents targeting human epidermal growth factor receptor 2.